Analysis of land use and land cover changes in the municipality of Araçuaí, Minas Gerais by means of remote sensing techniques in the years 2000 and 2019 - Pacheco, Dhiego Gonçalves (2021)
The study aimed to analyze the changes in land use and land cover in the municipality of Araçuaí, Minas Gerais, through satellite images obtained by remote sensing. The images used were from the Landsat 5 satellite, TM sensor, referring to the year 2000 and Landsat 8, OLI sensor, relative to the year 2019. The ArcGIS 10.8 software was used for the digital processing of the images and the supervised classification, from the samples selected in the images. Four land use classes were established: dense vegetation, undergrowth, exposed soil/urbanized area, and water bodies. For the period studied, the results show a reduction in the classes dense vegetation (1,49%), undergrowth (6,32%) and water bodies (0,25%), and consequently, expansion of the class exposed soil /urbanized area (8,07%). In this sense, it is highlighted that remote sensing techniques constitute as an important tool for prior knowledge and continuous monitoring of the changes occurring in the landscape, contributing to actions of planning, land-use planning and environmental preservation in the municipality.